2020
DOI: 10.1016/j.cell.2020.04.024
|View full text |Cite
|
Sign up to set email alerts
|

The Genomic History of the Bronze Age Southern Levant

Abstract: Highlights d Analysis of genome-wide data for nine sites from the Bronze Age Southern Levant d Contemporaneous samples from multiple sites are genetically similar d Migration from the Zagros and/or Caucasus to the Levant between 2500-1000 BCE d People related to these individuals contributed to all presentday Levantine populations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 61 publications
(68 reference statements)
7
58
0
Order By: Relevance
“…One of these mutations was detected in a 4,000-year-old mummy from Deir el-Bersha, Egypt also assigned to this haplogroup 65 , raising the possibility that the presence of U5b2b5 at Kulubnarti reflects deep connections with Egypt; other mtDNA haplogroups, including J2a2e, R0a1, T1a7, U1a1, and U3b are also found both at Kulubnarti and in ancient Egyptians 31 . U1a1, U3b, and N1b1a2 have also been identified in Bronze Age individuals from Israel and Jordan 42 , so the presence of these lineages also at Kulubnarti is consistent with the genome-wide data. Previously-published ancient Egyptian data in ref.…”
Section: Resultssupporting
confidence: 81%
“…One of these mutations was detected in a 4,000-year-old mummy from Deir el-Bersha, Egypt also assigned to this haplogroup 65 , raising the possibility that the presence of U5b2b5 at Kulubnarti reflects deep connections with Egypt; other mtDNA haplogroups, including J2a2e, R0a1, T1a7, U1a1, and U3b are also found both at Kulubnarti and in ancient Egyptians 31 . U1a1, U3b, and N1b1a2 have also been identified in Bronze Age individuals from Israel and Jordan 42 , so the presence of these lineages also at Kulubnarti is consistent with the genome-wide data. Previously-published ancient Egyptian data in ref.…”
Section: Resultssupporting
confidence: 81%
“…This example highlights how the vagaries of discovery and issues of representativeness influence mobility studies, and it is important to keep in mind that only a small portion of the total number of ancient inhabitants of the city has been recovered to date and is available for sampling. Nevertheless, this study has revealed multiple scales and levels of mobility at Alalakh in the Middle and Late Bronze Age, and shows, as have other recent studies in the ancient Near East [139,141,215], that the majority of sampled individuals were locals who likely lived, died, and were buried in close proximity to the place where they were born. This has important implications for understanding individual mobility in the Near Eastern Bronze Age: while such mobility is documented at relatively high levels both textually and archaeologically, it seems that -within the range and limitations the methods discussed here…”
Section: Discussionsupporting
confidence: 71%
“…The Middle East and the Arabian Peninsula are pivotal regions in the timeline of human history and an increasing number of aDNA studies have attempted to understand the genetic history in these regions. Although there have been successful studies 1,[3][4][5][6][7][8][9][10][11][12][13][14] , given the poor conditions for DNA preservation, this process is proving to be slower than in more environmentally favourable regions of the world. Nonetheless, given the historical importance of this region, each newly recovered DNA sequence adds an important piece to the genomic and cultural puzzle of this territory.…”
Section: Discussionmentioning
confidence: 99%
“…In the Arabian Peninsula and North Africa, the proportion of African ancestry increases. Different archaeogenetic studies have highlighted the complex demographic changes that have shaped genomic ancestry in the Levant 1,[3][4][5][6][7][8][9][10][11][12][13][14] .The majority of prehistoric and historic genomes sequenced so far follow a similar pattern, but several studies have also found single individuals deviating from this pattern 6,8,11 . Such finds suggest additional small-scale migrations and the presence of structure within the region that is not displayed in the majority of the past society.…”
Section: Genomic Ancestry Of Levantine Populationsmentioning
confidence: 99%
See 1 more Smart Citation